Innocentric Health Sdn. Bhd / Anis Izzati Ramli … [et al.] - Ramli, Anis Izzati; Syukri, Muhammad Faris Syazwi; Ahmad Tamizi, Nur Awatif; Mohamad Zainuddin, Nur Syafinie; Ramli, Nur Syakirah (2022)
A face mask business called Innocentric Health Sdn. Bhd. intends to launch operations in Shah Alam, Malaysia. When Innocentric Health was founded, its mission was to produce high-quality products that are worth their price and function for the targeted market. Other than that, the company believes that helping patients from any dangerous viruses by providing security to help them keep safe should be prioritized first. Despite that, they also believe that a healthier future generation that is free from any contagious viruses could be created. Our vision is to protect the community from being affected by the virus spread in the air, especially for those who have bad respiratory conditions such as asthma, occupational lung disease, and chronic obstructive pulmonary disease (COPD). The company will be led by Nur Syafinie as Chief Executive Officer led and followed by Muhammad Faris as Administration Manager, Anis Izzati as Operation Manager, Nur Syakirah as Financial Manager, and Nur Awatif as Marketing Manager. The ownership structure of Innocentric Health is a corporation with a 5-member board of directors. The group members are willing to overcome any challenges and are always encouraging one another. Each member will bear an equal degree of responsibility in the event of a loss. To share the same losses, there must be an equal division of ownership. Each member will therefore be accountable for 20% of the overall ownership percentage. Each member additionally committed to contributing RM80,000 in equity, for a total investment in the equity of RM400,000. We aim to market a smart face mask with many special features as our primary item. The brand name of the high-tech health item, created by our company, is Meliora The Mask. It was created with a focus on leading a healthy lifestyle so that users could live better lives without being constrained by anything while being informed of their health conditions. Meliora is a recommended face mask that has an air purifier system, can remove any micro dust and germs, and can guard against viral illnesses. Due to its dual-fan mechanism, which blows air in accordance with your breathing rate, it can also improve breathing and make it simpler to breathe fresh air. This is especially appropriate for exercising and engaging in physical activities like jogging. Additionally, the design was incredibly comfortable and breathable. When speaking, Meliora, our product, has a clear speech system. This makes it possible to speak with confidence, project your voice more clearly and loudly, and make it simple for others to hear you. To allow for repeated use, it may also be recharged. The built-in, high-capacity battery provides up to 6 hours of operation before needing to be recharged, which takes two hours. We will give clear and comfortable face mask air filter replacement components for recurrent use since it is a one-time purchase. When not in use, the special charging case for Meliora The Mask's UV light-coated interior eliminates germs and viruses. The existence of Bluetooth connectivity enables you to track your breathing directly to your smartphone as well as learn about the maintenance of your product to maximize usage. It also offers Wi-Fi. A GPS from Meliora can be connected to your smartphone immediately, and an app named "Go Mazk'' can also be connected to customers' cell phones directly. Customers can use the app to instantly find a missing face mask. Customers can track their respiration rate using "Go Mazk," which will offer cautions and suggestions. Additionally, it will provide an alert regarding the quantity of dust, bacteria, and viruses, among other duties. We have already made the decision to advertise the product to those who are suffering from respiratory conditions such as asthma, chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, pneumonia, and lung cancer. In order to assist those who are experiencing post-covid symptoms including breathing difficulties, coughing, and shortness of breath, we also focus on them. The majority of Meliora's customers are people who have breathing problems. Most technological health products will have devoted users, and Meliora demonstrates this. Customers will continually replace the replacement components, or if the mask breaks, they might buy a new one or buy it for their family. Our products are easy to obtain, consumers can find us directly from our website at www.innocentricshop.com or easily on our social media, Facebook and Instagram as this is the most efficient approach to attract customers and offer consulting and follow-up services to ensure customer satisfaction with our product. We are aware of how crucial it is to achieve distinctive product standards that will guarantee excellent business performance. Since our face mask is comfortable, unique, modern, and provides better protection, we believe we have delivered higher consumer happiness and given ourselves a competitive advantage. In addition, we offer a higher quality product at an affordable price. Our business will be able to compete with other brands on the market.